A CONCEPTUAL FRAMEWORK FOR USING TIKTOK TO FACILITATE AUTONOMOUS VOCABULARY LEARNING AMONG EFL LEARNERS - Janastasya, Lathifa Khania; Arif Suryo Priyatmojo (Universitas PGRI Palembang, 2025)
This paper introduces a new perspective on how TikTok can be utilized to facilitate autonomous English vocabulary learning, offering an alternative to traditional pedagogical methods that often lack student engagement and practical relevance. Through a synthesis of previous studies and a review of key learning theories, this paper proposes a conceptual framework grounded in the assertion that TikTok serves as a valuable educational resource by integrating three foundational concepts: Vygotsky's social learning theory, Schmitt's vocabulary learning strategies, and Benson's theory of autonomous learning. In essence, TikTok's unique features such as its interest driven algorithm and authentic content, create an environment where students can engage in self-directed learning and apply strategic techniques for effective vocabulary acquisition. Therefore, an understanding of this theoretical synthesis can empower educators to guide students in transforming TikTok from a mere entertainment application into an intentional tool for language learning. This framework aims to provide educators with new insights for developing innovative pedagogies suited to the digital habits of contemporary students, while also establishing a foundation for future research.